Defining Extreme Events: A Cross‐Disciplinary Review. Issue 3 (10th March 2018) - McPhillips, Lauren E.; Chang, Heejun; Chester, Mikhail V.; Depietri, Yaella; Friedman, Erin; Grimm, Nancy B.; Kominoski, John S.; McPhearson, Timon; Méndez‐Lázaro, Pablo; Rosi, Emma J.; Shafiei Shiva, Javad
Abstract: Extreme events are of interest worldwide given their potential for substantial impacts on social, ecological, and technical systems. Many climate‐related extreme events are increasing in frequency and/or magnitude due to anthropogenic climate change, and there is increased potential for impacts due to the location of urbanization and the expansion of urban centers and infrastructures. Many disciplines are engaged in research and management of these events. However, a lack of coherence exists in what constitutes and defines an extreme event across these fields, which impedes our ability to holistically understand and manage these events. Here, we review 10 years of academic literature and use text analysis to elucidate how six major disciplines—climatology, earth sciences, ecology, engineering, hydrology, and social sciences—define and communicate extreme events. Our results highlight critical disciplinary differences in the language used to communicate extreme events. Additionally, we found a wide range in definitions and thresholds, with more than half of examined papers not providing an explicit definition, and disagreement over whether impacts are included in the definition. We urge distinction between extreme events and their impacts, so that we can better assess when responses to extreme events have actually enhanced resilience. Additionally, we suggest that all researchers and managers of extreme events be more explicit in their definition of such events as well as be more cognizant of how they are communicating extreme events. We believe clearer and more consistent definitions and communication can support transdisciplinary understanding and management of extreme events. Plain Language Summary: Extreme events, such as heat waves, widespread flooding, or very strong storms, are of interest to scientists and managers because of their potential to cause extensive damage and impacts on people, infrastructure, and nature. With climate change causing more of these events to happen, it is important that we understand how or when they might occur, and how to better respond to them to prevent disastrous impacts. For these reasons, researchers from many different subject areas study extreme events. However, we show that researchers from different backgrounds may use very different words to communicate about these events and different ways of deciding what makes an extreme event "extreme." In order for researchers, managers, and planners to help everyone better prepare for and respond to extreme events, we encourage all researchers to improve how they explain why they are studying a particular event and make greater effort to understand the work that colleagues in other subject areas are doing and how that may affect our own research and practice. Key Points: What constitutes an extreme event varies by study and discipline; thus we must be explicit in how we define extreme events Extreme events are often conflated with their impacts, but this will inhibit future recognition of resilience Bridging across disciplinary differences in communication and definitions is critical for holistic management of extreme events